POWER AND ABILITY IN INCREASING COMPLIANCE; THE ORIGIN OF LEADERS’ INFLUENCE IN PESANTREN - Akmal Mundiri; Ana Muthmainnah (Managere: Indonesian Journal of Educational Management, 2021)
This study aims to understand the strengths and abilities of leaders in increasing the obedience of their subordinates through the study of figures, namely KH. Moh. Zuhri Zaini is the caretaker of the Nurul Jadid Paiton Islamic Boarding School. This study uses a qualitative approach to character study. Data were obtained from a collection of biographies about KH. Moh. Zuhri Zaini and interviews with his subordinates who act as administrators at the Nurul Jadid Islamic Boarding School Paiton, Probolinggo, East Java. The results showed the strength of KH. Moh. Zuhri Zaini, in making his subordinates obedient, is charismatic, authoritative, inspiring, and humble. The goal is to understand the character of a person KH. Zuhri Zaini about his strength and ability to make his subordinates obedient by recognizing his subordinates. This research is also an additional insight and reference for leaders in influencing the compliance factor of their subordinates.